Protocol for a cohort study to evaluate the effectiveness and cost-effectiveness of general population screening for cardiovascular disease: the Viborg Screening Programme (VISP). Issue 2 (28th February 2023) - Høgh, Annette; Lindholt, Jes Sanddal; Søgaard, Rikke; Refsgaard, Jens; Svenstrup, Dorte; Moeslund, Niels-Jørgen; Bredsgaard, Mette; Dahl, Marie
Abstract : Introduction: The prevalence of cardiovascular disease (CVD) is increasing. Furthermore, asymptomatic individuals may not receive timely preventive initiatives to minimise the risk of further CVD events. Paradoxically, 80% of CVD events are preventable by early detection, followed by prophylactic initiatives. Consequently, we introduced the population-based Viborg Screening Programme (VISP) for subclinical and manifest CVD, focusing on commonly occurring, mainly asymptomatic conditions, followed by prophylactic initiatives. The aim of the VISP was to evaluate the health benefits, harms and cost-effectiveness of the VISP from a healthcare sector perspective. Furthermore, we explored the participants' perspectives. Methods and analysis: From August 2014 and currently ongoing, approximately 1100 men and women from the Viborg municipality, Denmark, are annually invited to screening for abdominal aortic aneurysm, peripheral arterial disease, carotid plaque, hypertension, diabetes mellitus and cardiac arrhythmia on their 67th birthday. A population from the surrounding municipalities without access to the VISP acts as a control. The VISP invitees and the controls are followed on the individual level by nationwide registries. The primary outcome is all-cause mortality, while costs, hospitalisations and deaths from CVD are the secondary endpoints. Interim evaluations of effectiveness and cost-effectiveness are planned every 5 years using propensity score matching followed by a Cox proportional hazards regression analysis by the 'intention-to-treat' principle. Furthermore, censoring-adjusted incremental costs, life-years and quality-adjusted life-years are estimated. Finally, the participants' perspectives are explored by semistructured face-to-face interviews, with participant selection representing participants with both negative and positive screening results. Ethics and dissemination: The VISP is not an interventional trial. Therefore, approval from a regional scientific ethical committee is not needed. Data collection from national registries was approved by the Regional Data Protection Agency (record no. 1-16-02-232-15). We ensure patient and public involvement in evaluating the acceptability of VISP by adopting an interviewing approach in the study. Trial registration number: NCT03395509 .